SOLVING ALGEBRAIC PROBLEMS USING THE CONCEPT OF A VECTOR - Qodirova Dilshodaxon Abdunabiyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article shows the possibilities of proving algebraic problems using the concept of a vector, in particular inequalities, solving a system of algebraic equations and equations, and finding the largest and smallest values of a function.